EXPLORING LANGUAGE STYLE IN THE MENU MOVIE: A COMPREHENSIVE STUDY - Cladhora Sharron Lauterboom; Cicih Nuraeni (PROJECT (Professional Journal of English Education), 2024)
Language style and language function have been the subject of substantial sociolinguistics research. The movie is one of the media utilized to analyze this point through characters. The main characters are the center of each movie’s constructed story. This study aims to identify the language style utilized by the main characters in The Menu movie, to identify the language function implemented through each style, and to determine which language style is used dominantly in the movie. This study employed a qualitative descriptive methodology. Language style and function are defined and identified using the theories of Martin Joos (1976) and Roman Jakobson (1980). The result revealed that the main characters employed the five categories identified by Martin Joos’ (1976) Language style theory: frozen style (9 data), formal style (18 data), consultative style (10 data), casual style (29 data), and intimate style (6 data). The data also revealed that the main characters made use of the six categories identified by Roman Jakobson (1980) in his theory of language function including referential function (24 data), emotional function (30 data), conative function (12 data), phatic function (8 data), metalingual function (4 data), and poetic function (4 data). The predominant language style is casual. Examining language style with different sources and theories can be done furthermore to fully comprehend the idea of language.